The Role of SMEs in Enhancing Women’s Employment Opportunities in Nepal: A Data-Driven Perspective - Sharma, Laxmi Kanta; Paudel, Vishal (Cognition, 2025)
Small and Medium Enterprises (SMEs) play a crucial role in Nepal’s economy, making up over 90% of all businesses and providing jobs for around 2.6 million people. Despite this, women are underrepresented in the SME sector, accounting for only 37.75% of the workforce. Most of these women work in informal and low-paying roles, highlighting a significant gender gap. This study takes a data-driven approach to explore the barriers that limit women’s participation in SMEs. These include restricted access to financial resources, insufficient vocational training, deeply rooted societal norms, and poor infrastructure in rural areas. By analyzing secondary data, the research emphasizes how promoting gender inclusion in SMEs could have transformative effects. These include reducing poverty, increasing household incomes, and potentially boosting Nepal’s GDP by up to 16%. The study also reviews successful practices from around the world and evaluates how they can be adapted to Nepal’s unique social and economic conditions. It calls for targeted measures such as expanding women’s access to financial services, providing skill development opportunities, and implementing gender-sensitive policies. These actions aim to create a more inclusive SME sector. Ultimately, the findings underline the critical role of SMEs in driving sustainable economic growth and gender equality. By prioritizing women’s participation, SMEs can become powerful tools for socioeconomic progress in Nepal